A Multilateral Regime for Space Resource Exploration and Utilization - Yun, Zhao (Indonesian Journal of International Law, 2020)
The launched of Sputnik marked the beginning of space race. Since then state always tries to develop its technology to conquer outer space, including its natural resources. Outer Space Treaty and Moon Agreement affirm that outer space as the common heritage of mankind. Therefore, any states can not claim sovereignty over the territory nor natural resources. Yet, in 2015 the United States passed the Space Resource Exploration and Utilization Act which authorize its private entities to exploit and entitles them with series of rights, including the right of ownership over space resource. Thus, this paper examines the concept of the “common heritage of mankind” (“CHM”) in the Agreement Governing the Activities of States on the Moon and Other Celestial Bodies (Moon Agreement) and elaborates on the possibility of a multilateral regime for space resource exploration and utilization. Part 2 discusses the concept of the CHM and its application; it then followed by an in-depth analysis of the future multilateral regime in Part 3. Part 4 concludes that a multilateral regime, instead of a unilateral regime, shall be in the best position to balance the needs for space resource exploration and the interests of developing countries.